Asuhan Keperawatan Gerontik Pada Pasien Dengan Dermatitis Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman Tahun 2026 - Hana Kultsum; Hasmita Hasmita; Armaita Armaita; Sandra Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to the World Health Organization (WHO, 2024), there are approximately 241 million cases of dermatitis worldwide, with 11 million cases affecting the elderly population. Data from the Indonesian Ministry of Health (2025) estimates that the number of elderly people suffering from dermatitis in Indonesia reaches around 2.1 million to 2.4 million individuals. Dermatitis is an inflammation of the epidermis and dermis layers of the skin characterized by itching and various skin abnormalities such as redness, dryness, and scaling. This condition commonly occurs in the elderly due to decreased skin function and may affect quality of life, including comfort, sleep, and daily activities. This study aimed to describe gerontic nursing care for dermatitis patients at the Tresna Werdha Sabai Nan Aluih Social Institution, Sicincin, Padang Pariaman Regency. The method used was a case study with a nursing process approach that included assessment, nursing diagnosis, planning, implementation, and evaluation. This study was conducted from February 11, 2026, to February 16, 2026. The research subject was Mr. A, a 61-year-old male with complaints of chronic itching on the folds of the arms and chest for the past 12 years. The assessment results showed the presence of reddish rashes, dry and scaly skin, and wounds caused by scratching. In addition, the client experienced limitations in activities due to weakness in the left extremities. The nursing diagnoses established included impaired skin/tissue integrity, impaired comfort, and self-care deficit. Nursing interventions were carried out in accordance with the Indonesian Nursing Intervention Standards (SIKI) and the Indonesian Nursing Outcome Standards (SLKI), including skin care, pruritus management, and self-care support. The evaluation results showed improvements in the patient’s condition, including reduced itching, increased comfort, and expected improvement in self-care abilities, although the problems were not completely resolved. In conclusion, appropriate and continuous nursing care can help improve the quality of life of elderly patients with dermatitis.